PENDAMPINGAN OLIMPIADE MATEMATIKA: STRATEGI PENGUATAN PENALARAN SISWA DAN KOMPENSI GURU PEMBINA SMP NEGERI 3 RAMBAH HILIR - Afri, Lusi Eka; Arcat, Arcat; Najmi, Zhafirah; Yuliana, Rika (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
A systematic mentoring relevant to the demands of mathematics olympiads based on reasoning. The purpose of this activity is to enhance students’ reasoning abilities, develop a cotextualized olympiad learning module, and strengthen the competencies of teacher coaches. The implementation method uses a participatory-educative approach, actively engaging both students and teachers at every stage of the activities. The activities consisted of training, simulated, and competitive motivation sessions based role models. Evaluation was conducted throught pre test and post test, observation, and perception survey. The result show that there were an increase inthe average score of student’s reasoning by 52% and the accuracy rate of answers increases from 47,8% to 82,5%. This improvements were supported by mentoring strategy used, which includes habituation of a gradual approach, pattern identification, and the application of systematic critical thinking logic. Qualitative results futher indicated that 85% of student reported greather confidence and 90% benefited simulation question. The learning module proved effective in assisting teachers to improve their mentoring techniques and facilitating students’ understanding of the material. The growth of intrinsic motivation shows that 70% of student are motivated to participate in similar competitions in the future. These findings confirm that directed mentoring based on logical exercises and reflection is effective not only in improving student’s readiness to face olympiads but also has potential to bulid a culture of critical learning and independent coaching in schools.